Rekayasa Augmented Reality Planet dalam Tata Surya sebagai Media Pembelajaran Bagi Siswa SMP Negeri 57 Palembang - Agmita Clara Rosa; Hastha Sunardi; Herri Setiawan (UNIVERSITAS INDO GLOBAL MANDIRI)
ABSTRACTInformation Technology Utilization in teaching materials is considered very helpful in providing science learning material about the type of solar system, the texture and layers that are inside the planet. Augmented reality technology is combines two-dimensional or 3-dimensional virtual objects into a real three-dimensional environment and then projects virtual objects in real time and takes place simultaneously. Showing material, the application can also display images of planets in 3D animation objects along with planetary layers and practice questions, using text books as markers for augmented reality with marker tracking methods that can be used on android. The method used from this application is the Rational Unified Process and modeling the Unified Modeling Language (UML). Using C# programming language for coding programs that will be used in making augmented reality. By building a system of simulating the solar system of the planet Bima Sakti as an iteractive learning media for students using an Android-based augmented reality technology that is effective in providing information about the descriptions of planets and planetary layers, it is hoped that there will be added value for students to get to know the Creator. By knowing how great the universe is, students will certainly be able to understand the vastness of this universe, which of course there will be awareness for students that the Creator of this universe, of course, is greater than his creation and more powerful over his creation. So that the material from this application can be combined with religious studies, especially Islamic Religion.Keywords : Augmented Reality, Solar System. Interactive learning, C # (C Sharp), RUPABSTRAKPemanfaatan Teknologi Informasi pada bahan ajar untuk siswa dinilai sangat membantu dalam memberikan materi pembelajaran IPA tentang sistem tata surya jenis, tekstur dan lapisan yang ada didalam planet. Teknologi Augmented Reality adalah teknologi yang mengabungkan benda maya dua dimensi ataupun 3 dimensi kedalam sebuah lingkungan nyata tiga dimensi lalu memproyeksikan benda-benda maya tersebut dalam waktu nyata dan berlangsung bersamaan. Menampilkan materi, aplikasi juga dapat menampilkan gambar planet dalam objek animasi 3D disertai lapisan planet dan latihan soal, menggunakan buku teks sebagai marker untuk augmented reality dengan metode marker tracking yang dapat digunakan diandroid. Metode yang digunakan dari aplikasi ini adalah Rational Unified Process dan pemodelan Unified Modeling Language (UML). Menggunakan bahasa pemrograman C# untuk coding program yang akan digunakan dalam pembuatan augmentedreality. Dengan membangun system simulasi tata surya planet Bima Sakti sebagai media pembelajaran iteraktif bagi siswa menggunakan teknologi augmented reality berbasis android yang efektif dalam memberikan informasi tentang deskripsi planet dan lapisan planet, diharapkan ada nilai tambah bagi siswa untuk lebih mengenal Sang Pencipta. Dengan mengenal betapa besar jagat raya ini, maka siswa tentunya akan dapat memahami begitu luasnya alam ini, yang tentunya akan ada kesadaran bagi siswa bahwa Sang Pencipta alam raya ini, tentunya lebih besar dari ciptaannya dan lebih berkuasa atas ciptaannya. Sehingga materi dari aplikasi ini dapat dikombinasikan dengan pelajaran agama, khususnya Agama Islam.Kata kunci : Augmented Reality, Tata Surya, Pembelajaran Interaktif, RUP